The Shepherd of Hermas - Lake, Kirsopp (Harvard theological review, 1925)
There is no danger that anyone will overlook the importance of Mr. Bonner's article on the Michigan Papyrus of the Shepherd of Hermas in the number of this Review for April, 1925. The publication of a manuscript of the Shepherd of Hermas dating from the third century will be a real event in the history of the interpretation of early Christian literature. But there is one point in his statement which, though it will appeal at once to those who have worked on the Shepherd, is likely to escape the notice of others unless attention be drawn to it.